Nanofiltrated C1‐esterase‐inhibitor in the prophylactic treatment of bradykinin‐mediated angioedema. Issue 5 (12th January 2016) - Greve, Jens; Hahn, Janina; Nordmann, Melanie; Schuler, Patrick J.; Bas, Murat; Hoffmann, Thomas K.; Hajdu, Zuzana; Buchberger, Maria; Strassen, Ulrich
Abstract : BACKGROUND: Patients suffering from bradykinin‐induced angioedema show recurrent swelling of subcutaneous and submucosal structures. Increased bradykinin levels lead to an increase in vascular permeability and edema formation. Current therapy consists of B2 bradykinin receptor antagonists, C1‐esterase‐inhibitor (C1‐INH) concentrate, or the kallikrein inhibitor ecallantide. In most cases the treatment of acute attacks is sufficient. Prophylactic therapy is recommended only in severe cases. C1‐INHc has been shown a safe and efficient option. Its effect on the quality of life has not yet been analyzed. STUDY DESIGN AND METHODS: Patients with inadequate disease control despite an "on‐demand therapy" including C1‐INHc and/or the B2 receptor antagonist icatibant were switched to long‐term prophylaxis consisting in an individual dose of intravenous C1‐INHc (Cinryze). None of the patients had been previously treated with ecallantide. Disease‐specific quality‐of‐life questionnaires and patient records were used for evaluation. Disease control, quality of life, adverse events, and administered dosage per month were compared for 6 months on on‐demand therapy and the following 6 months under prophylactic therapy. RESULTS: Data of seven patients with hereditary angioedema (HAE) and one patient with acquired angioedema were evaluated. Prophylactic therapy with Cinryze led to a significant and clinically relevant reduction in the overall attack frequency from 6.7 to 2.3 per month without relevant side effects. The frequency of severe attacks was reduced by 89% and quality of life significantly improved. CONCLUSION: Prophylaxis with Cinryze led to a significantly improved quality of life in our cohort of patients with high‐frequency bradykinin‐induced angioedema attacks that were not sufficiently treated with on‐demand medication.